Copy Number Variation Analysis in Turkish Patients with Congenital Bilateral Absence of Vas Deferens - Semra Kahraman; Mehmet Murad Başar; Yiğit Akın; Durkadın Demir Ekşi; Elanur Yılmaz; Mustafa Faruk Usta; Munire Erman; Özgül M. Alper (Acta Medica Alanya)
Aim: Congenital Bilateral Absence of the Vas Deferens (CBAVD) is a developmental abnormality that causes infertility in males. According to the literature, up to 88% of CBAVD cases have at least one pathogenic Cystic Fibrosis Transmembrane Conductance Regulator gene (CFTR) mutation. However, based on our previous data, this rate was 15.90% in Turkish patients with CBAVD. We aimed to identify genomic copy number variations (CNV) and candidate genomic regions which could related to the CBAVD in Turkish population.Methods: CNV analysis was performed in 19 Turkish CBAVD patients normal karyotypes and a wild type CFTR genotype. We suggested that the DAD1 gene may be a candidate gene related to CBAVD by reviewing online databases and analyzing CNV findings. Sanger sequencing of the DAD1 gene exons was performed in 22 patients.Results: We identified 11 CNVs that most likely related with the disease in nine of 19 (47.3%) patients. As the most common CNV, 14q11.2 deletions were detected in there (15.79%) of the patients. There was only DAD1 gene in the sharing genomic region of two of the 14q11.2 deletions. No sequence variation was detected in the DAD1 gene of the patients.Conclusion: The 14q11.2 chromosomal region and the DAD1 gene may be associated with CBAVD. Further studies are needed to indentify the contribution of CNVs and DAD1 gene to CBAVD etiology.